New data on the Afrotropical Xantholinini. 3. New species from Ethiopia of the Naturkundemuseum, Erfurt (Coleoptera, Staphylinidae) - Bordoni, Arnaldo (Contributions to Entomology = Beiträge zur Entomologie, 2019)
Xantholinini of Ethiopia preserved in the Erfurt Naturkundemuseum were studied. The following new species are described and illustrated: Leptacinus riza spec. nov., Gyrohypnus aethiopicus spec. nov., G. oromianus spec. nov., Notolinopsis aethiopicus spec. nov., N. dodolanus spec. nov., Balchis oromiana spec. nov. and B. hartmanni spec. nov. Nomenclatur acts Leptacinus riza spec. nov. – urn:lsid:zoobank.org:act:CAEFF2A7-4E7E-435E-A27B-6A1B7DECB5C7 Gyrohypnus aethiopicus spec. nov. – urn:lsid:zoobank.org:act:B522E05B-83CE-40ED-9BB2-6B8889346129 Gyrohypnus oromianus spec. nov. – urn:lsid:zoobank.org:act:BB7E6499-4CFF-4284-AE1A-D93B06FA703F Notolinopsis aethiopicus spec. nov. – urn:lsid:zoobank.org:act:8023CD1F-4527-4606-93CF-95B0DCFEE682 Notolinopsis dodolanus spec. nov. – urn:lsid:zoobank.org:act:963F9C5A-8967-4309-9DAA-1BB3D34766D6 Balchis oromiana spec. nov. – urn:lsid:zoobank.org:act:504C405E-7F96-477E-96EC-334336EBFC05 Balchis hartmanni spec. nov. – urn:lsid:zoobank.org:act:13B9745D-404D-4037-BC3A-642C3BDB5D60